Use of Bruckner Test for the Detection of Significant Refractive Errors in Children - Mubashar Jalis,Muhammad Waqas Ashfaq,Anjum Imdad (Journal of Rawalpindi Medical College, 2015)
Background : To evaluate the potential use of the Buckner test to detect significant refractive errors in infants and children. Methods: In this prospective study Bruckner test was performed, in children upto 15 years of age, with direct ophthalmoscope and position and size of pupillary crescent was noted. Subsequently, non-cycloplegic and cycloplegic auto-refraction was performed using auto-refracto-meter. Children were classified according to errors of refraction, Emmetropic, Myopic and Hyperopic. Results: Total 102 children were included, 56 males and 46 females with mean age of 8.38 years. Results of Bruckner test, revealed 50 (49.0%) right eyes hyperopic and 35(34.3%) myopic, 53 (51.9%) left eyes were hyperopic and 36 (35.2%) myopic. Cycloplegic auto-refraction revealed significant hyperopia in 48 and 50 right and left eyes respectively. Significant Myopia was detected in 30 and 27 right and left eyes. The sensitivity and specificity of Bruckner test to detect refractive errors in children was found to be 97% and 79% respectively. Conclusion: The Bruckner test has potential usefulness, reasonable accuracy, timeliness and simplicity as a screening test to detect refractive errors in children.